Development of the 4E-FTE Engine Simulator Trainer to Improve Learning Outcomes through Problem Based Learning - Tohadi, Tohadi; Samani, Muchlas; Susila, I Wayan (International Journal for Educational and Vocational Studies, 2020)
This research aims development of the 4E FTE simulator trainer and peripheral equipment which is integrated with the problem based learning model from validated 4D Models trainer simulators: (1) pedagogical aspects; (2) conceptual aspects and; (3) conceptual aspects. Developed trainer simulator is able to improve cognitive, affective and psychomotor domains of learning outcomes. Questionnaire and student achievement test were used as research instruments. Data analysis was performed to determine the level of validity, practicality and student learning outcomes which include learning outcomes in the cognitive, affective and psychomotor domains. This research found some evidence (1) There was no significant difference in cognitive domain learning outcomes using the 4E FTE engine simulator trainer which was compared to learning outcomes using the engine stand with a mean value of 82.36 and for the engine stand class with a cognitive mean value of 80.55; (2) Based on affective domain learning outcomes for students who use the 4E FTE engine simulator trainer perspective, there were significant differences compared to students who learn using the engine stand, with an affective domain mean value of 85.64, mean engine stand of affective value 84.62, and; (3) There was no significant difference between the Problem Based Learning (PBL) model using the 4E FTE engine trainer simulator with the engine stand on psychomotor student learning outcomes. The mean value of the psychomotor domain was 79.39 while the mean value of the psychomotor was 78.64.